The Third Way and Feminist Imaginings - Joyce Stalker (Adult Education Research Conference, 2000)
The Third Way purports to be a new way which merges the best elements of social democracy and neo-liberalism. Although it is an extremely ambiguous concept, it clearly exhibits androcentric characteristics. Its ambiguity offers adult educators the opportunity to influence its direction and operationalisation in order to improve the dis-location of women.